Case Report: Long-Term Response to Pembrolizumab Combined With Endocrine Therapy in Metastatic Breast Cancer Patients With Hormone Receptor Expression - Wu, Dingyong; Tang, Shu; Ye, Rong; Li, Dongmei; Gu, Dejian; Chen, Rongrong; Zhang, Huan; Sun, Jianguo; Chen, Zhengtang (Frontiers in Immunology, 2021)
Breast cancer is one of the most commonly diagnosed malignancies. Although endocrine therapy improves the survival of patients with hormone receptor (HR)-positive breast cancer, the post-endocrine therapy strategy for metastatic breast cancer remains challenging. Herein, we report two patients who benefited from antiestrogen agents combined with an immunotherapy regimen to support the notion that an immunotherapy combination regimen may be a potential treatment for patients with HR-positive metastatic breast cancer post-endocrine therapy. Case 1 involved a patient with relapsed breast cancer with ovarian and brain metastases after endocrine therapy. After undergoing surgery for the ovarian lesions, she received three cycles of chemotherapy. Given that the lesions in the brain did not change, chemotherapy was discontinued. A high T cell receptor (TCR) repertoire (high Shannon index and clonality) was observed in the tumor. Considering the patient's preference and safety, and the efficacy of immunotherapy, she was administered with letrozole combined with pembrolizumab. The patient achieved a partial response, and the progression-free survival (PFS) was more than 21 months. Case 2 involved a patient with breast cancer with multiple bone metastases. After failure of combined radiotherapy and chemotherapy, the patient received tamoxifen combined with pembrolizumab based on the patient's preference and clinical biomarkers of a positive differentiation cluster of eight tumor-infiltrating lymphocytes and a high TCR repertoire (high Shannon index and clonality) in the tumor. The patient's bone pain and biomarkers were relieved after the treatment. The patients completed six cycles of pembrolizumab, and the PFS was more than 21 months. In conclusion, our study confirmed that antiestrogen agents combined with an immunotherapy regimen is a promising treatment for patients with HR-positive metastatic breast cancer.